2008
DOI: 10.1002/jmv.21333
|View full text |Cite
|
Sign up to set email alerts
|

In vitro use of autologous dendritic cells improves detection of T cell responses to hepatitis B virus (HBV) antigens

Abstract: T lymphocyte responses to hepatitis B virus (HBV) core antigen (HBcAg) are vigorous and easily detectable in vitro during recovery from acute hepatitis B but significantly weaker in patients with chronic HBV infection. In contrast, T cell responses to hepatitis B surface antigen (HBsAg) are almost undetectable during infection and even in a substantial fraction of subjects receiving vaccination with HBsAg. The aim of this study was to investigate whether the use of dendritic cells (DCs) in an in vitro assay co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…17 Similarly, other studies have shown that autologous moDCs loaded with recombinant HBV antigens were capable of stimulating autologous T-cell proliferation. [37][38][39] Because of their stimulatory capacity, moDCs loaded with recombinant antigens or synthetic peptides have been administered to patients in two clinical trials. In both cases, a significant improvement in virological parameters was observed in approximately 50% of the patients, with the HBeAg-negative patients responding best.…”
Section: Potential Of Modc Vaccinesmentioning
confidence: 99%
“…17 Similarly, other studies have shown that autologous moDCs loaded with recombinant HBV antigens were capable of stimulating autologous T-cell proliferation. [37][38][39] Because of their stimulatory capacity, moDCs loaded with recombinant antigens or synthetic peptides have been administered to patients in two clinical trials. In both cases, a significant improvement in virological parameters was observed in approximately 50% of the patients, with the HBeAg-negative patients responding best.…”
Section: Potential Of Modc Vaccinesmentioning
confidence: 99%
“…This strategy may be extended to other persistent infections and potentially open new avenues for immunotherapy. Currently, in vitrocultured moDCs loaded with recombinant antigens have been used to vaccinate patients with chronic HBV (47,48), HCV (49), and HIV (50-52) infection. These vaccines can enhance virus-specific T cell responses, but are hindered by the need to select appropriate antigens and a GMP cell production facility to produce the vaccine.…”
Section: Figurementioning
confidence: 99%
“…In consideration of its immunomodulatory potential [4], IFN-a is predicted to act rapidly on HBV-specific T-cell responses since the effect on the immune system is direct rather than only indirectly mediated by the decline of viremia and antigenemia. However, little is known about the behavior of protective antiviral T-cells during the early phases of IFN therapy in e antigen (HBeAg)-negative genotype D chronic hepatitis B, since most published studies [5][6][7][8][9][10] have been focused on HBeAg-positive patients, who can have a different immunological reactivity to IFN, and have been conducted with a limited set of immunological assays, which can be inadequate to characterize thoroughly the IFN effect. Therefore, our study was done on a homogeneous group of HBeAg-negative genotype D CHB patients with positive baseline predictors of response to IFN, who should also have maximal probability of immunological improvement during therapy, using a comprehensive set of immunological parameters to avoid the risk of missing some effects of IFN therapy on T-cells.…”
Section: Introductionmentioning
confidence: 99%